The role of the social state in enhancing civic responsibility in society - Saydullayevich, Botirov Zafar (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study examines the role of the social state in enhancing civic responsibility within the framework of social state theory. It highlights how the state safeguards citizens’ rights while fostering moral, spiritual, and social obligations necessary for active civic engagement Methodology/approach: A qualitative descriptive approach is applied through document analysis of scholarly literature, legislative frameworks, and policy reports. Comparative analysis is used to explore how different social state models contribute to strengthening civic responsibility. Results/findings: The findings show that a social state significantly promotes civic responsibility by ensuring social protection, equal educational opportunities, family upbringing support, and avenues for political engagement. It establishes reciprocal obligations between state and citizens, fostering social stability and shared ethical values. Conclutions: The social state is not limited to enforcing legal compliance but plays a key role in cultivating civic awareness and encouraging participation in societal development. Its effective implementation enhances civil society, protects fundamental rights, and supports collective responsibility. Limitations: This study is theoretical, lacking empirical validation through field research or case studies, which may limit its generalizability. Contribution: This article enriches political and social theory by clarifying the functional importance of the social state in advancing civic responsibility and offering conceptual insights for policy development in modern governance.